2022
DOI: 10.3389/fimmu.2021.817132
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evaluation of HLA-G 3’Untranslated Region Variants in Locally Advanced, Non-Metastatic Breast Cancer Patients: UTR-1, 2 or UTR-4 are Predictors for Therapy and Disease Outcome

Abstract: Despite major improvements in diagnostics and therapy in early as well as in locally advanced breast cancer (LABC), metastatic relapse occurs in about 20% of patients, often explained by early micro-metastatic spread into bone marrow by disseminated tumor cells (DTC). Although neoadjuvant chemotherapy (NACT) has been a successful tool to improve overall survival (OS), there is growing evidence that various environmental factors like the non-classical human leukocyte antigen-G (HLA-G) promotes cancer invasivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…HLA-G is an inhibitory checkpoint molecule, which is highly expressed in gynecological cancers, such as cervical cancer ( 3 , 4 , 7 10 ), ovarian cancer ( 20 ), breast cancer ( 21 , 22 ), and endometrial cancer ( 23 ). It’s known that virus-infected cells and malignant cells escape the host’s immune surveillance by inducing the expression of HLA-G ( 4 6 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…HLA-G is an inhibitory checkpoint molecule, which is highly expressed in gynecological cancers, such as cervical cancer ( 3 , 4 , 7 10 ), ovarian cancer ( 20 ), breast cancer ( 21 , 22 ), and endometrial cancer ( 23 ). It’s known that virus-infected cells and malignant cells escape the host’s immune surveillance by inducing the expression of HLA-G ( 4 6 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cytospin preparations, containing single cell suspensions derived from mononuclear bone marrow cells of TNBC patients, were used for genomic DNA extraction by QIAamp DNA Blood Mini Kit (Qiagen, Hilden, Germany) according to manufacturer’s instructions. Typing of HLA-G 3’ UTR haplotype was performed by polymerase chain reaction (PCR) as previously described ( 39 , 43 ). Typing of the ILT-2 rs10416697C/G SNPs located distant from ILT-2 gene promoter region was determined by a Taqman assay (ThermoFisher Scientific) according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…In non-metastatic locally advanced BC patients including a total of 18% TNBC patients, our study group recently demonstrated that high levels of vesicular-bound HLA-G before CT were associated with stem cell like CTC as well as with early disease progression ( 38 ). Moreover, certain HLA-G 3’ UTR haplotypes were found to predict therapy and disease outcome in that patient cohort ( 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…The value of chemotherapy for node‐positive BC patients has been well established 3 . Neoadjuvant chemotherapy (NAC) can downstage primary tumors and axillary nodes, increase the eligibility for breast‐conserving surgery and improve the survival of patients with locally advanced BC 4–9 . However, it remains unclear whether there are the same survival and prognosis between patients with the same stages after NAC and at initial diagnosis, especially in pT1‐2N1M0 BC 10 .…”
Section: Introductionmentioning
confidence: 99%
“… 3 Neoadjuvant chemotherapy (NAC) can downstage primary tumors and axillary nodes, increase the eligibility for breast‐conserving surgery and improve the survival of patients with locally advanced BC. 4 , 5 , 6 , 7 , 8 , 9 However, it remains unclear whether there are the same survival and prognosis between patients with the same stages after NAC and at initial diagnosis, especially in pT1‐2N1M0 BC. 10 Previous studies showed that the 5‐year LRFS, DMFS and OS rates of patients with de novo T1‐2N1 BC were 86.8%, 91.0%, and 83.8%, respectively, 11 yet rare studies have explored the survival outcomes of post‐chemotherapy ypT1‐2ypN1 BC patients.…”
Section: Introductionmentioning
confidence: 99%